Teaching English Humanely: An Experiment in Interaction in English Teacher Preparation - Richard G. Hause (Educational Considerations, 1975)
Student-centered teaching techniques were used with a group of English teachers to develop interaction. The objective was to make the teaching and learning of English more palatable, more fun, and more exciting.